"Holes in my Memories": A Qualitative Study of Men Affected by Father Absence. (1st August 2014) - East, Leah; Jackson, Debra; Power, Tamara; Woods, Andrew; Hutchinson, Marie
<x xml:space="preserve">Abstract</x> This qualitative study explored adult men's experiences of father absence. Interviews with 21 men between the ages of 24 and 70 explored narratives of father absence and how the men perceived this influenced their life trajectory. Thematic analysis revealed that these men experienced a range of difficulties and challenges, including episodes of sadness and depression associated with loss and grief for the paternal relationship, self-esteem issues, feelings of anger and rejection, and difficulty forming trusting relationships particularly with other men. This study contributes to understanding mental health issues that can be associated with paternal absence for men.